Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3389/fpsyg.2020.02073
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Virtual Reality Technology on the Imagery Skills and Performance of Target-Based Sports Athletes

Abstract: The aim of this study is the examination of the effect of virtual reality based imagery (VRBI) training programs on the shot performance and imagery skills of athletes and, and to conduct a comparison with Visual Motor Behavior Rehearsal and Video Modeling (VMBR + VM). In the research, mixed research method and sequential explanatory design were used. In the quantitative dimension of the study the semi-experimental model was used, and in the qualitative dimension the case study design was adopted. The research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 126 publications
(123 reference statements)
0
24
0
1
Order By: Relevance
“…This will be crucial for implementation and dissemination of VR in regular clinical practice. A recent study of Bedir and Erhan (2021) on the effect of a VR training programme on the performance of athletes showed that the participants in the VR condition improved significantly compared to those in the video training condition. However, this must be studied more closely before making any statements about it.…”
Section: Discussionmentioning
confidence: 99%
“…This will be crucial for implementation and dissemination of VR in regular clinical practice. A recent study of Bedir and Erhan (2021) on the effect of a VR training programme on the performance of athletes showed that the participants in the VR condition improved significantly compared to those in the video training condition. However, this must be studied more closely before making any statements about it.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Im et al ( 2016 ) reported that virtual-reality-guided MI of a wrist extension task increased cortical excitability in both stroke patients and healthy participants more than MI alone. Similarly, Bedir and Erhan ( 2021 ) reported significant improvements in shot accuracy in curling, bowling and archery athletes following VR-based imagery relative to Visual Motor Behavior Rehearsal and Video Modeling. In addition, it was noted that the VR component may have contributed to participants adapting to imagery training earlier due to the enhanced simulation of kinesthetic, visual and auditory senses.…”
Section: Virtual Reality For Motor Imagerymentioning
confidence: 91%
“…We have ushered in a new era, but in terms of the number of national publications, there is still a big gap with European and American countries, which is mainly limited by differences in economic conditions, cultural background, and scientific research capabilities. In general, every year, new countries join the research of virtual reality technology, which can be divided into the following three stages [ 15 ]. Development period: since 2012, emerging countries such as Iran, Saudi Arabia, Lithuania, Pakistan, and Jordan have also begun to work on virtual reality research [ 16 ].…”
Section: Virtual Reality Technology and Related Research Progressmentioning
confidence: 99%